Pop Art in Animation Behind the Iron Curtain: - Andreas Trossek (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2023)
In this essay, Andreas Trossek, an art historian and critic, writes about psychedelic animation from Estonia.